Exploring the acceptability and perception by dog owners towards the appearance of dry dog food - Gomez Baquero, David (Kansas State University, 2018)
Sensory analysis techniques play a key role in the pet food industry to ensure the final product meets both the pets’ and pet owners’ demands and expectations. To date, the study of the pet owners’ perception towards pet foods is still an emerging field of study and a few number of publications have been released on the topic. In particular, little research has been conducted on exploring the pet owners’ perception regarding the appearance of pet foods. The objective of this work is to study the effect of the visual characteristics of dry dog food on the acceptability and perception by consumer segments of dog owners in the US and in Poland and to explore whether differences exist within countries and across the two countries. For this purpose, dog owners in both locations evaluated the appearance of thirty dry dog food samples with varying visual properties. The participants rated their degree of acceptability towards the appearance of the samples with four different attributes using 9-point hedonic scales. Also, the consumers were asked to associate each one of the samples with a list of positive and negative beliefs on a check-all-that-apply question. Cluster Analysis, ANOVA, and Correspondence Analysis were used to analyze the consumer feedback. The results demonstrate that the acceptability of the appearance of dry dog food is affected by the number of different kibbles present, color(s), shape(s), and size(s) in the product. Similarities were found both within countries and across countries and consumer segments. Consumers overall showed a preference for single-kibble samples of medium brown colors, medium kibble sizes, low-dimensional contrast kibbles and traditional kibble shapes. Furthermore, extra-small or extra-large sized kibble sizes and kibble shapes with a high-dimensional contrast were rejected by the consumers overall. In addition, differences across consumer segments within countries and across countries were identified from the results. The findings indicate that this topic have possibly been overlooked and opportunities for further research on this field are identified. Dry dog food manufacturers should take special consideration with the appearance of their products to enhance the acceptability by dog owners. The outcome of this work can help to drive dry dog food companies meet consumers’ needs and demands in a constantly changing pet food market, with benefits anticipated to the pet food industry and the wellbeing of dog owners.
Keywords: Sensory analysis